Preoperative Hemoglobin Level Predicts Surgical Site Infections in Trauma Orthopedic Surgery: A Cohort Study - Williams Walana; Fredrick Gyilbagr; Alexis D. B. Buunaaim (Journal of Tropical Medicine)
Conclusion: In conclusion, our study demonstrates that preoperative hemoglobin level is a useful hematological parameter for predicting surgical site infection following trauma orthopedic surgery. These inexpensive and common hematological parameters could assist in guiding preventive efforts to reduce surgical site infections and improve outcomes for vulnerable patients undergoing trauma orthopedic surgery. Assessing preoperative hemoglobin levels is crucial in identifying patients at increased risk of developing surgical site infections. Preoperative optimization, including incorporating hemoglobin levels into predictive risk models can help to assess these at-risk persons better. Educate patients on the need to optimize their hemoglobin levels before surgery and discuss potential interventions, including iron supplementation or transfusion.